Relative Performance Evaluation and Competitive Aggressiveness - FEICHTER, CHRISTOPH; MOERS, FRANK; TIMMERMANS, OSCAR (Journal of Accounting Research, 2022)
ABSTRACT We examine the relation between incentive plans based on relative performance and competitive aggressiveness. Using data on executive incentive‐compensation contracts in large U.S. firms, we find a positive association between competitive aggressiveness and peer group overlap—that is, the extent to which two firms select each other as peers in these incentive plans. Our findings indicate that managers of such firms take more frequent as well as more complex competitive actions, relative to managers evaluated on relative performance without peer group overlap. Moreover, we show that these competitive tactics are more pronounced when managers compete against: (1) peers with similar grant sizes, (2) peers on similar performance metrics, and (3) peers in the same industry. Collectively, our findings provide evidence on how widely used incentive‐compensation practices relate to strategic firm decisions.